Kościół rzymskokatolicki w Polsce północno-wschodniej (województwo białostockie, łomżyńskie i suwalskie) a przemiany polityczne, społeczno-gospodarcze i prawne przełomu lat 1988–1989 - Sychowicz, Krzysztof (Komunizm: System - Ludzie - Dokumentacja, 2023)
The Communist authorities’ search for a way out of the permanent crisis of the late 1980s prompted them to start talks with some of the opposition circles existing at the time, and to make related legal, social and political changes. Contributions to the changes taking place in the provinces of Białystok, Łomża and Suwałki were also made by the clergy and lay members of the Roman Catholic Church. This was the institution which was perceived most negatively by the government of the time. In the situation after the military coup of 13 December 1981, the Church turned out to be a true asylum of freedom for believers and non-believers. By making the churches available, it became the main patron of culture and art, as well as a major philanthropist. Charitable aid was organised in parishes and monasteries all over Poland for the interned and arrested activists of the Solidarity trade union. The turn of 1989 undoubtedly influenced the changes, and above all the activation of the activities carried out by the Roman Catholic Church. From its position as a limited mediator between the opposition and the Communist authorities, it was faced with the task of calming the dissatisfaction expressed by part of society and explaining the purpose of the ongoing talks to the rest. This was not easy, especially as many clergymen did not believe in the sincere intentions of the authorities; they correctly assumed that the Communists were making another attempt to strengthen their position in the whole process. However, many priests saw even the semi-democratic electionsas an opportunity to reduce the scope of control which the government exercised over society.